Pre-injury assessment of everyday executive function in moderate to severe traumatic brain injury. Issue 7 (9th August 2019) - Hart, Tessa; Rabinowitz, Amanda R.; Whyte, John; Kim, Junghoon
ABSTRACT: Executive dysfunction is frequently observed in moderate to severe traumatic brain injury (TBI) and is commonly assessed with objective measures or subjective rating scales. Given the variability in executive function in the normal population, a reliable measure of pre-injury executive function would be of considerable value. In this study we examined pre-injury self and collateral (relative or friend) ratings on the Frontal Systems Behavior Rating Scale (FrSBe). Fifty-one persons with moderate to severe TBI and their collaterals provided before- and after-TBI ratings at 3 months post injury. A subset of 36 dyads were retested at 6 and 12 months; 26 neurologically intact controls and their collaterals also provided FrSBe ratings. At 3 months post injury, the difference between patient and collateral ratings of current status was larger than the difference relating to premorbid status, suggesting that patients were able to rate themselves from a pre-injury perspective. However, pre-injury ratings from collaterals were more reliable over time compared with patients' self-ratings. For all sets of ratings – before injury, after injury, and status of healthy controls – collateral ratings indicated more abnormality, overall, than comparable self-ratings. Evaluating one's own executive behaviour may be a difficult task even without TBI, with the difficulty exacerbated by the effects of injury.